HIV/AIDS epidemic in India and predicting the impact of the national response: Mathematical modeling and analysis - Arni S. R. Srinivasa Rao; Kurien Thomas; Kurapati Sudhakar; Philip K. Maini (Mathematical Biosciences and Engineering)
After two phases of AIDS control activities in India, the thirdphase of the National AIDS Control Programme (NACP III) was launchedin July 2007. Our focus here is to predict the number of peopleliving with HIV/AIDS (PLHA) in India so that the results can assistthe NACP III planning team to determine appropriate targets to beactivated during the project period (2007-2012). We have constructeda dynamical model that captures the mixing patterns betweensusceptibles and infectives in both low-risk and high-risk groups inthe population. Our aim is to project the HIV estimates by takinginto account general interventions for susceptibles and additionalinterventions, such as targeted interventions among high riskgroups, provision of anti-retroviral therapy, and behavior changeamong HIV-positive individuals. Continuing the current level ofinterventions in NACP II, the model estimates there will be 5.06million PLHA by the end of 2011. If 50 percent of the targets inNACP III are achieved by the end of the above period then about 0.8million new infections will be averted in that year. The currentstatus of the epidemic appears to be less severe compared to thetrend observed in the late 1990s. The projections based on thesecond phase and the third phase of the NACP indicate preventionprogrammes which are directed towards the general and high-riskpopulations, and HIV-positive individuals will determine the declineor stabilization of the epidemic. Model based results are derivedseparately for the revised HIV estimates released in 2007. Accordingto revised projections there will be 2.08 million PLHA by 2012 if 50percent of the targets in NACP III are reached. We perform aMonte Carlo procedure for sensitivity analysis of parameters andmodel validation. We also predict a positive role of implementationof anti-retroviral therapy treatment of 90 percent of the eligiblepeople in the country. We present methods for obtaining diseaseprogression parameters using convolution approaches. We also extendour models to age-structured populations.